Development and characterization of a thermophilic, lignin degrading microbiota. (December 2017) - Ceballos, Shannon J.; Yu, Chaowei; Claypool, Josh T.; Singer, Steven W.; Simmons, Blake A.; Thelen, Michael P.; Simmons, Christopher W.; VanderGheynst, Jean S.
Graphical abstract: Highlights: Thermophilic microbial communities were cultivated on a high-lignin feedstock. Compositions of bacterial and fungal communities and enzyme activities were measured. Relative abundances of lignin decomposition and tolerance genes were predicted. The dominant bacterium identified with enrichment was from the genus Rubrobacter . The dominant fungus identified with enrichment was from the genus Talaromyces . Enriched and dominant bacteria contained lignin decomposition and tolerance genes. Abstract: Microbial communities and associated enzymes that hydrolyze lignocellulose in the presence of lignin decomposition products are important for industrial and environmental bioconversion processes. The aims of this study were to identify microorganisms capable of decomposing lignocellulose and tolerating lignin decomposition products under high-solids and thermophilic conditions, and to elucidate potential mechanisms of tolerance. High-solids incubations were conducted to enrich for thermophilic communities that decompose Douglas fir. Bacterial and fungal communities were determined using 16S rRNA and ITS region gene sequencing, and PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) was applied to predict genes involved in lignocellulose degradation and tolerance to lignin decomposition products. Lignin decomposition increased with enrichment of specific microorganisms. The dominant bacterium identified with enrichment was from the genus Rubrobacter while the dominant fungus was from the genus Talaromyces . Bacteria containing predicted genes associated with lignin degradation and tolerance to breakdown products were identified. These included organisms from the genus Rubrobacter, and families Beijerinckiaceae and Xanthomonadaceae . The dominant bacteria and fungi identified may be promising sources of enzymes that degrade lignocellulose and genes that confer tolerance to lignin decomposition products.